Effects of metaverse-based career mentoring for nursing students: a mixed methods study - Yujeong Kim; Mi Young Kim (BMC, 2023)
Abstract Background There is a lack of studies on metaverse-based career mentoring for college students in both quantitative and qualitative research. This study aimed to examine the effect of metaverse-based career mentoring among nursing students and explore the experiences of mentors and mentees. Methods This study used a mixed methods design using both a survey for collecting quantitative data and focus group interviews for a qualitative one. A total of 8 mentors and 43 mentees participated in the metaverse-based career mentoring program. The program covered eight career fields and was delivered across eight sessions of 60 min each, over six days. Career decision-making self-efficacy among mentees and platform and program satisfaction were measured before and after the program. Afterwards, 7 mentors and 12 mentees participated in the focus group interviews to investigate their experience of participating in the metaverse-based career mentoring program. Quantitative data were analyzed using descriptive statistics, paired t-test, Wilcoxon signed-rank test, and Mann-Whitney U test. The qualitative data underwent thematic analysis. Results After the metaverse-based career mentoring program, mentees' career decision-making self-efficacy increased significantly compared to the baseline level. From the mentor-mentee focus group interviews, three key themes were derived: (i) communicating frankly and openly, (ii) being satisfied with realistic communication and program functions, and (iii) expecting an even more optimized program. Conclusions A metaverse-based career mentoring program for nursing students can have a positive effect on their career decision-making self-efficacy. In addition, in terms of education, it is helpful as a non-face-to-face medium and feeling a sense of reality, so it is expected that it will be beneficial in education by applying various contents in the future.